Analysis of the Implementation of Enhancing the Competitiveness of Halal SMEs in Indonesia - Wardiyah, Mia Lasmi; Fauziah, Sofia Maryam; Utami, Sinbi Fitria; Subagja, Haifa Aulia Nurshafiyyah; Rosmayanti, Maya (Dinasti Publisher, 2025)
The halal industry in Indonesia has experienced rapid growth and plays a significant role in strengthening the national economy. As the country with the largest Muslim population in the world, the demand for halal products continues to rise, particularly among Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the implementation of Sharia principles in enhancing the competitiveness of halal MSMEs in Indonesia. The research employs a descriptive qualitative method using a literature review and secondary data analysis sourced from official institutions such as BPS, BPJPH, and KNEKS in 2025. The findings indicate that the implementation of Sharia principles which encompass halal compliance, justice, transparency, and business ethics has a positive impact on strengthening the competitiveness of halal MSMEs. The food and beverage subsector grew by 5.68% (year-on-year) and contributed 18.67% to the national GDP, while 9.8 million products had been certified halal as of October 2025. In addition, the total Islamic financial assets reached IDR 10,774 trillion, accounting for 28.6% of the total national financial assets, with a 12.8% (yoy) growth rate. These findings demonstrate that the application of Sharia principles enhances the credibility, efficiency, and competitiveness of halal MSMEs both nationally and globally. Nevertheless, the study identifies several challenges, such as low halal literacy among MSME actors, limited digitalization in the certification process, and insufficient collaboration among supporting institutions. Therefore, strengthening strategies through digitalization of certification services, entrepreneur education, and implementation of self-declaration programs are essential steps to promote the development of halal MSMEs that are inclusive, competitive, and sustainable.